Vertical dynamics of free-living and particle-associated vibrio communities in the eastern tropical Indian Ocean - Zhu, Shaodong; Wang, Xiaolei; Zhao, Wenbin; Zhang, Yulin; Song, Derui; Cheng, Haojin; Zhang, Xiao-Hua (Frontiers in Microbiology, 2023)
Members of the family Vibrionaceae (vibrios) are widely distributed in estuarine, off-shore and marginal seas, and perform an important ecological role in marine organic carbon cycle. Nevertheless, there is little knowledge about whether vibrios play ecological roles in the oligotrophic pelagic area which occupied a larger water volume.In this study, we investigated the abundance, diversity and composition of free-living and particle-associated vibrios and their relationships with environmental factors along the water depth in the eastern tropical Indian Ocean (ETIO). The vibrios abundance of free-living fractions was significantly higher than that of particle-associated fractions in surface, but both were similar in bottom, indicating that vibrios may shift from freeliving lifestyles in surface to mixed lifestyles in bottom. Vibrio-specific 16S rRNA gene amplicon sequencing revealed that Paraphotobacterium marinum and V. rotiferianus were dominant species in water column, and V. parahaemolyticus (a clinically important pathogen) was recorded in 102 samples of 111 seawater samples in 10 sites, which showed significant difference from the marginal seas. The community composition also showed shift with depths in water column. Paraphotobacterium marinum decreased with the depth and V. rotiferianus OTU1528 was mainly distributed in deeper water, which significantly correlated with the alteration of environmental factors (e.g., temperature, salinity and dissolved oxygen). Besides temperature and salinity, dissolved oxygen (DO) was also an important factor affecting the composition and abundance of Vibrio communities in the ETIO. Our study revealed the vertical dynamics and preferential lifestyles of vibrios in the ETIO, helping to fill a knowledge gap on their ecological distribution in oligotrophic pelagic areas and fully understand the response of vibrios in a global warming environment.